Lead Intoxication in Free-Ranging Bald Eagles (Haliaeetus leucocephalus). Issue 2 (March 2019) - Manning, Leah K.; Wünschmann, Arno; Armién, Anibal G.; Willette, Michelle; MacAulay, Kathleen; Bender, Jeff B.; Buchweitz, John P.; Redig, Patrick
Lead toxicity due to ingestion of spent ammunition is an ongoing cause of mortality in bald eagles. While gross and histologic lesions of lead intoxication have been described in a few individuals of this species, the prevalence of lesions is underreported. A retrospective study of 93 bald eagles with severe lead intoxication was performed to describe the associated lesions and their prevalence and to compare the lesions with blood, liver, kidney, and/or bone lead concentrations. Gross lesions associated with lead toxicity were most frequent within the heart (51/93 birds) and consisted of multifocal myocardial pallor and rounding of the apex. Within the brain, gross lesions included petechiae or hemorrhagic necrosis (13/93 birds). Histologic lesions compatible with lead toxicity occurred within the heart (76/93 birds), brain (59/93 birds), and eyes (24/87 birds). Lead toxicity in bald eagles is characterized by fibrinoid necrosis of small- to medium-caliber arteries, most commonly affecting the heart, brain, and eyes. Gross and histologic lesions are consistent with ischemia caused by a primary vascular injury. A blood lead concentration of greater than 4 ppm and markedly elevated liver lead concentrations were associated with a greater likelihood of lesions in the heart. Severe lead intoxication is frequently associated with lesions that are histologically detectable in bald eagles. The presence of fibrinoid arterial necrosis and parenchymal degeneration, necrosis, and/or hemorrhage within the heart, brain, and/or eyes is suggestive of lead toxicity in bald eagles and warrants evaluation of liver or bone lead concentrations.